Public Health in Eastern Europe: Visible Modernization and Elusive Gender Transformation. Issue 1 (1st March 2020) - Unknown
Abstract : Heike Karge, Friederike Kind-Kovacs, and Sara Bernasconi, eds., From the Midwife's Bag to the Patient's File: Public Health in Eastern Europe, Budapest: Central European University Press, 2017, vii–xix, 349 pp., $70.00/€62.00 (hardback), ISBN: 978-963-386-208-7. Constantin Barbulescu, Physicians, Peasants, and Modern Medicine: Imagining Rurality in Romania, 1860–1910, translated by Angela Jianu, Budapest: Central European University Press, 2018, xi–xii, 292 pp., $60.00/€50.00 (hardback), ISBN: 978-963-386-267-4.